2024
DOI: 10.1021/acs.iecr.3c03931
|View full text |Cite
|
Sign up to set email alerts
|

Multifidelity Gaussian Processes for Predicting Shear Viscosity over Wide Ranges of Liquid State Points Based on Molecular Dynamics Simulations

Maximilian Fleck,
Joachim Gross,
Niels Hansen

Abstract: A linear multifidelity model based on Gaussian process (GP) regression is proposed that uses shear viscosities from a few molecular dynamics simulations as well as a few experimental shear viscosities to enable a highquality prediction of this transport property over a large range of thermodynamic state points. Transport properties, such as viscosity, determined from molecular simulations are sensitive to the underlying force field, which is often parametrized with emphasis on vapor−liquid coexisting propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Hence deviations between model prediction and experimental references are of systematic quantitative nature. This qualifies the outputs of the models proposed in this work as low fidelity inputs of a multi-fidelity model as proposed in previous work [Fleck et al, 2024].…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Hence deviations between model prediction and experimental references are of systematic quantitative nature. This qualifies the outputs of the models proposed in this work as low fidelity inputs of a multi-fidelity model as proposed in previous work [Fleck et al, 2024].…”
Section: Resultssupporting
confidence: 76%
“…Our previous multi-fidelity work has shown that the entropy space is very beneficial for machine learning applications as it translates a complex two-dimensional problem with phase boundaries into a continuous low-dimensional space [Fleck et al, 2024]. Some side results are worth mentioning with regard to this work.…”
Section: Entropy Scalingmentioning
confidence: 92%
See 1 more Smart Citation
“…Numerical values and corresponding standard deviations are given in Supporting Information Table S5. PC-SAFT parameters and multifidelity predictions based on previous work are shown in Table S6 and Figure S16.…”
Section: Resultsmentioning
confidence: 99%
“…When used in MD simulations, the hydrogen mass needs to be assigned to the position of the hydrogen atom. Transport coefficients such as shear viscosity or thermal conductivity were not considered during force field optimization and some deviations to experimental data are observed. , …”
Section: Methodsmentioning
confidence: 99%